Leprosy in Brazil in the 21st century: analysis of epidemiological and operational indicators using inflection point regression, - Carlos Dornels Freire de Souza; João Paulo Silva de Paiva; Thiago Cavalcanti Leal; Gabriel da Silva Urashima (Sociedade Brasileira de Dermatologia, 2020)
Abstract The objective of this study was to analyze the trend of epidemiological and operational indicators of leprosy in Brazil, from 2001 to 2017. This was a time series study involving nine indicators. The inflection point regression model was used. Decreasing trends were observed for the following: general detection (−4.8%), children under 15 (−3.7%), prevalence (−7.0%), and grade 2/million inhabitants (−3.5%). The proportion of individuals with grade 2 disability showed an upward trend (2.0%) from 2001 as well as contacts examined from 2003 (5.0%). The proportions of cure and of individuals with a degree of disability assessed at the time of the diagnosis and the cure showed a stationary behavior. Although advances are noted, there are still challenges to be overcome.